2021
DOI: 10.1111/papr.12992
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Root Ganglion Stimulation Normalizes Measures of Pain Processing in Patients with Chronic Low‐Back Pain: A Prospective Pilot Study using Quantitative Sensory Testing

Abstract: Background Dorsal root ganglion stimulation (DRG‐S) is used as a treatment for chronic low‐back pain (CLBP), although its underlying mechanisms remain elusive. CLBP patients have been found to have reduced mechanoreceptive perception, reduced endogenous analgesia, as well as deep‐tissue hyperalgesia when compared with healthy controls. Using quantitative sensory testing (QST), we studied if DRG‐S in CLBP patients results in changes in pain processing. Methods Quantitative sensory testing was performed in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…This very low frequency dependent nerve fiber type activation was recently demonstrated in the rodent model, where C fiber propagation into the dorsal horn was entrained up to 20 Hz, and further activation was not achieved up to 100 Hz (74). Additionally, it was demonstrated that hypersensitivity to mechanical stimulation normalizes with DRG‐S, a phenomenon recently demonstrated in patients implanted with DRG‐S using pressure pain threshold testing (74,75).…”
Section: Very Low‐frequency Drg‐s: Spinal Inhibitionmentioning
confidence: 84%
“…This very low frequency dependent nerve fiber type activation was recently demonstrated in the rodent model, where C fiber propagation into the dorsal horn was entrained up to 20 Hz, and further activation was not achieved up to 100 Hz (74). Additionally, it was demonstrated that hypersensitivity to mechanical stimulation normalizes with DRG‐S, a phenomenon recently demonstrated in patients implanted with DRG‐S using pressure pain threshold testing (74,75).…”
Section: Very Low‐frequency Drg‐s: Spinal Inhibitionmentioning
confidence: 84%
“…Early ambulation to decrease postoperative infections is an accepted practice that has repeatedly been demonstrated in systematic reviews 56,57 . DRG‐S has demonstrated greater improvements in physical function, as measured by disability scores, 21,58–62 compared to SCS 63–65 . Robust improvements in functional status may thus relate to low infection rates.…”
Section: Discussionmentioning
confidence: 98%
“…A similar rapid appearance of migrations was observed in SCS and improved with anchor placement. 3,4 DRG-S has been shown to significantly improve function, 11,12,28,29 and likely led to a restoration of activities and quality of life shortly after implantation.…”
Section: Migrationsmentioning
confidence: 99%